(untitled) (CIPEEX, 2025)
Abstract Patient safety is a fundamental pillar of quality in health care, especially in surgical settings. Based on WHO guidelines, the Brazilian National Health Surveillance Agency (ANVISA) implemented the Safe Surgery Protocol, which includes a checklist applied at three critical moments: before anesthesia, before the incision, and before leaving the operating room. This report describes the experience of three medical students during an observational activity at a private hospital in Anápolis, Brazil, involving an elective surgery for abdominal wall endometrioma removal. The students participated exclusively in the application of the surgical safety checklist, following institutional standards. The preoperative phase was conducted appropriately, including review of exams, informed consent, fasting verification, and anesthetic assessment, although the responsible physician’s signature was missing. During the first checklist step, all items were correctly followed. In the second step, hand hygiene, sterilization, and communication were adequate, but the operating room door remained open, compromising environmental control. The final checklist stage was completed with precision, and the patient was transferred to the recovery room in stable condition. The surgery was performed without major complications, and the excised tissue was sent for histopathological analysis. This experience reinforced the critical role of the surgical safety checklist in reducing adverse events and ensuring coordinated, humanized care. Although most protocols were followed correctly, specific failures, such as the lack of the physician’s signature and open door during the procedure, highlight the importance of continuous education and strict adherence to safety standards. The integration between theory and practice provided valuable learning, enabling students to understand the dynamics of the operating room and the importance of effective communication and protocol compliance. The observation also emphasized how active student participation contributes to improving care processes and fostering a culture of safety. This report contributes to the literature by presenting a real-world experience of checklist implementation and by encouraging professional training focused on safety and quality in surgical care.